Green Product Development and Product Portfolio Management: Empirical Evidence from an Emerging Economy - Jugend, Daniel [UNESP]; Rojas Luiz, Joao Victor [UNESP]; Chiappetta Jabbour, Charbel Jose; a Silva, Sérgio Luis; Lopes de Sousa Jabbour, Ana Beatriz; Salgado, Manoel Henrique [UNESP] (Wiley, 2017)
Few studies have explored the relationship between green products development (GPD) and product portfolio management (PPM). When considering evidence from emerging economies, the knowledge gap is even deeper. Consequently, the objective of this work is to analyze how green and traditional practices of new product development (NPD) influence product portfolio and NPD performance. In addition, we explore how GPD opens new markets and technology opportunities. The empirical evidence is based on a sample of firms that are developing products and belong to innovative industrial sectors in Brazil. In general, the framework developed and tested in this research indicates the following: (i) the adoption of GPD practices significantly influences product portfolio performance; (ii) the adoption of GPD practices tends to generate positive results with regard to obtaining technological and market opportunities; (iii) the adoption of traditional PPM practices influences the dependent factors. Unexpectedly, correlations between a firm's size or age and its performance were not confirmed. This is the first empirical evidence relating GPD, PPM, and market and technology opportunities in Brazil. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment.
Keywords: eco-design; new product development; product portfolio; sustainable design